Biostratigraphic, paleoclimatic and paleobatymetric events in the upper continental slope, north Bahia, Brazil - Araújo, Tânia Maria Fonseca; Machado, Altair Jesus (Anuário do Instituto de Geociências, 2006)
Abstract